Comparison of a new enzyme-linked immunosorbent assay method with counterimmunoelectrophoresis for detection of teichoic acid antibodies in sera from patients with Staphylococcus aureus infections. - Herzog, C (1984)
Ribitol-teichoic acid antibodies were measured by a new enzyme-linked immunosorbent assay (ELISA) and by counterimmunoelectrophoresis in serum samples from 47 patients with serious Staphylococcus aureus infections, 63 infected patients, and 177 healthy controls. The same antigen was used for both tests. The group of patients with S. aureus endocarditis (6 patients) had significantly higher ELISA readings than the patients with other deep-seated infections (26 patients) or with an uncomplicated S. aureus bacteremia (15 patients). The patients with other serious gram-positive (40 patients) or gram-negative (23 patients) infections did not differ from the healthy control group. There were only three (7.5%) low-level cross-reactions among the infections caused by gram-positive organisms other than S. aureus. Of 46 initially ribitol-teichoic acid antibody-negative patients followed up for 2 weeks or more, only those developing a serious S. aureus infection showed a significant rise of the ELISA reading. There was a good correlation between ELISA and counterimmunoelectrophoresis. Both tests could be useful in the diagnosis and the management of complicated S. aureus infections. The ELISA method is, however, more sensitive and usually reflects the antibody rise after an infection earlier than does counterimmunoelectrophoresis.